Analisis Pemilihan Kost Ideal Khusus Putra Dengan Pemeringkatan Menggunakan Metode Topsis - Indra Riyana Rahadjeng (Universitas Asahan, 2021)
Decision making must of course be based on several factors that have a positive or no detrimental effect later. Therefore, careful calculations and considerations are required. This decision-making can occur in every human life, one of which is in deciding a temporary residence or boarding house for students who are studying outside the city. In this study, the selection of the ideal male boarding house was chosen as the object of research by using several factors as consideration. . Among them are the facilities provided, the balance of costs, distance, comfort level, security, and cleanliness. One solution to make it easier for students to choose and determine the appropriate, ideal and appropriate boarding house is to use decision support that can be done using the TOPSIS (Technique Order Preference by Similarity To Ideal Solution) method. This method is based on various concepts of the best alternative provided that it has the shortest distance to the positive ideal solution and the longest distance to the negative ideal solution. The researchers ranked and the result was that A2 boarding house was ranked the highest as the boarding house that best matched the search criteria so that it could be an alternative for students to choose after calculating using the TOPSIS method.